2019
DOI: 10.1097/md.0000000000015890
|View full text |Cite
|
Sign up to set email alerts
|

The prescription patterns of traditional Chinese medicine for women with polycystic ovary syndrome in Taiwan

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disease of reproductive-age women, accounting for about 9% to 18% of all women in this age group. Hyperandrogenemia, oligomenorrhea, or amenorrhea or anovulation, and polycystic ovary morphology are the 3 main criteria used to diagnose PCOS currently. Substantial scientific evidence and consensus on treating Taiwanese PCOS was lacking. The aim of this study is to investigate the characteristics and utilization of traditional Chinese medicine (TCM) among Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Herba Leonuri, also named Chinese Motherwort, has been widely used for the treatment of dysfunctional uterine bleeding, dysmenorrhea, polycystic ovary syndrome and other gynecological diseases for hundreds of years ( Lin et al, 2017 ; Lin et al, 2019 ). It has been reported that chemical components, including alkaloids, phenolic acids, flavonoids, as well as volatile oil and tannins, have been isolated and identified in Herba Leonuri (Wang et al, 2013; Wojtyniak et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Herba Leonuri, also named Chinese Motherwort, has been widely used for the treatment of dysfunctional uterine bleeding, dysmenorrhea, polycystic ovary syndrome and other gynecological diseases for hundreds of years ( Lin et al, 2017 ; Lin et al, 2019 ). It has been reported that chemical components, including alkaloids, phenolic acids, flavonoids, as well as volatile oil and tannins, have been isolated and identified in Herba Leonuri (Wang et al, 2013; Wojtyniak et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…TCM has a long history in treating menstrual diseases and infertility related to PCOS and has achieved good effects 12 Evidence-Based Complementary and Alternative Medicine [56]. In this study, several network pharmacology-based methods were used to predict potential targets.…”
Section: Discussionmentioning
confidence: 99%
“…45 Besides, PCOS patients were prescribed with the most popular JWXYS formula (38%) using an average daily dose of 6.1g. 46…”
Section: Jia-wei-xiao-yao-san Formula Indicationsmentioning
confidence: 99%